Sagot :
[tex]\large{\mathcal{SOLUTION:}}[/tex]
Equation: f = kgh
[tex] \\ [/tex]
Given: f = 15 , g = 3 , h = 1
STEP 1: Find for the constant k
- f = kgh
- 15 = k(3)(1)
- 15 = 3k
- 15/3 = k
- 5 = k
[tex] \\ [/tex]
Given: f = ? , g = 6 , h = 9 , k = 5
STEP 2: Find for the unknown
- f = kgh
- f = 5(6)(9)
- f = 270
Therefore , the value of f is 270
[tex] \\ [/tex]
[tex]\large{\mathcal{ANSWER:}}[/tex]
- f = 270
[tex] \\ [/tex]
✒️[tex]\large \bold{QUESTION} [/tex]
F varies jointly as g and h. If f = 15 when g = 3 and h = 1, find f when g = 6 and h = 9?
=============================
✒️[tex]\large \bold{ANSWER} [/tex]
- F = 270
=============================
✒️[tex]\large \bold{SOLUTION} [/tex]
Step 1 : Formulate
Based on the given conditions formulate
f = kgh
----------------------------------------
Step 2 : Subtitute
- f = 15
- g = 3
- h = 1
- into f = kgh:
15 = k × 3
----------------------------------------
Step 3 : Solve the Equation
15 = k × 3
k × 3 = 15
[tex]k = \frac{15}{3} [/tex]
k = 5
----------------------------------------
Step 4 : Find the Function
Find the equation of the function.
- f = 5gh
----------------------------------------
Step 5 : Subtitute
- Subtitute g = 6 into f = 5gh
----------------------------------------
Step 6 : Solve the Equation
- f = 5 × 6 × 9
- f = (5 × 6) × 9
- f = 30 × 9
- = 270
----------------------------------------
- So the Correct Answer is 270